Time interval moderates the relationship between psyching-up and actual sprint performance - Hammoudi-Nassib, S.; Chtara, M.; Nassib, S.; Briki, W.; Hammoudi-Riahi, S.; Tod, D.; Chamari, K. (The Journal of Strength and Conditioning Research, 2014)
This study attempted to test whether the strongest effect of psyching-up (PU) strategy on actual sprint performance can be observed when the strategy is used immediately (or almost) before performance compared with when there is a delay between PU and performance. To do so, 16 male sprinters (age, 20.6 ± 1.3 years; body mass, 77.5 ± 7.1 kg; height, 180.8 ± 5.6 cm) were enrolled in a counterbalanced experimental design in which participants were randomly assigned to 10 sessions (2 [Experimental Condition: imagery vs. distraction] × 5 [Time Intervals: no interval, 1 minute, 2 minutes, 3 minutes, and 5 minutes]). Before performing the experimental tasks, participants rated: (a) the Hooper index, (b) their degree of self-confidence, and (c) after the completion of the experimental test; they rated their perceived effort. Findings showed that the imagery significantly improved sprint performance. Specifically, the imagery enhanced performance on the phase of acceleration (0-10 m) and on the overall sprint (0-30 m) when used immediately before performance and at 1- and 2-minute intervals but not for 3- and 5-minute intervals. These findings support the hypothesis that the potential effect of the PU strategy on performance vanishes over time. The pre-experimental task Hooper and self-efficacy indexes did not change across the 10 experimental sessions, reinforcing the view that the observed performance changes were directly caused by the experimental manipulation and not through any altered status of the athletes (self-efficacy, fatigue/recovery, and stress). The potential mechanisms underlying such a process and practical applications are discussed.